Importance Of Globalization Process in Social Life - Panjiev Suhrob (Peerian Journals Publishing, 2024)
This article presents opinions on the philosophical foundations of the globalization process and its essence. Also, is highlighted the importance of proper use of convenience and opportunities brought by the process of globalization
Keywords: Globalization; global problems; globalization